Preface for Pertanika Journal of Social Sciences and Humanities: A Special Edition Devoted to Issues in Criminal Justice in the 21st Century: Spirit, Form & Challenges - Abdul Ghani Azmi, Ida Madieha; Zawawi, Majdah; Zulhuda, Sonny (UPM Press, 2015)
This Issue comprises of selected papers from the International Conference on Law, Order and Criminal Justice, which took place on 19th and 20th November 2014, at the beautiful ISTAC Campus. The Conference was hosted by the Ahmad Ibrahim Kulliyyah of Laws, IIUM, in collaboration with the Malaysian Judiciary, the Royal Malaysian Police, the Institute of Public Security Malaysia (IPSOM) and the National Council of Professors. The Conference focused on the modern criminal justice system with the aim of looking at the effectiveness of this existing system as a comprehensive system of controlling crimes and ensuring the safety of the public through various institutions, which are directed at maintaining social order and minimising crimes. In lieu of the challenges of the current criminal justice system, this Conference adopted the term “Law, Order and Criminal Justice” to cover all the different agencies and organisations involved in enforcing law and order, preventing crimes and meting out punishments, as well as how they work together in establishing the principles of equity, fairness and justice.